2021
DOI: 10.3390/ijerph181910245
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress, Dental Health, and Dental Fear among Finnish University Students: A National Survey

Abstract: The aim of this study was to study the association between dental fear, psychological distress, and perceived symptoms of teeth controlled for age, gender, educational sector, and tobacco use. The data from the Finnish University Student Health Survey 2016 targeting students (n = 10,000) of academic universities and universities of applied sciences were used. Psychological distress was measured with the Clinical Outcomes in Routine Evaluation 10 (CORE-10) and the General Health Questionnaire 12 (GHQ-12) and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
(100 reference statements)
2
8
0
Order By: Relevance
“…Female PASS students reported significantly higher GHQ-12 total scores, a result that is in agreement with several reports that female university students have significantly worse mental health than male students, regardless of the field of study or country (Eskin et al, 2016;Pohjola et al, 2021;Rodríguez-Romo et al, 2022;Zhang et al, 2022). However, in this study, high GHQ-12 scores were found in both women and men, suggesting the presence of high levels of psychological disorders or poor mental health.…”
Section: Discussionsupporting
confidence: 92%
“…Female PASS students reported significantly higher GHQ-12 total scores, a result that is in agreement with several reports that female university students have significantly worse mental health than male students, regardless of the field of study or country (Eskin et al, 2016;Pohjola et al, 2021;Rodríguez-Romo et al, 2022;Zhang et al, 2022). However, in this study, high GHQ-12 scores were found in both women and men, suggesting the presence of high levels of psychological disorders or poor mental health.…”
Section: Discussionsupporting
confidence: 92%
“…However, unlike other studies indicating the vulnerability of women to DFA, 23,29 no significant difference in IDAF‐4C scores were discerned between genders. Besides social, cultural and hormonal factors, the gender disparity in DFA has also been explained by higher levels of psychological distress and somatization among women 29,30 . The insignificant difference in DFA scores observed in our study could be attributed to the relatively small percentage of male responders (12.6%), which was consistent with the work of Smith specifying that women are more likely to participate in online surveys than men 31 .…”
Section: Discussionsupporting
confidence: 88%
“…Thirty articles examined the association between DFA and general anxiety/fear ( n = 11 pediatric, n = 19 adult). The majority of both pediatric [ 43 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] and adult studies [ 29 , 39 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] reported a relationship between DFA and general anxiety/fear. Only one pediatric study [ 69 ] and two adult studies [ 13 , 70 ] found no significant association between general anxiety/fear and DFA.…”
Section: Resultsmentioning
confidence: 99%